Hidden Curriculum in Islamic Religious Education: Religious Character and Responsibility through School Ecosystem Interconnection - Lutfina Aribah; Nur Munajat; Muhammad Ghozil Aulia; Ichsan Ichsan; Susiana Susiana (Al-Qalam Institue, 2026)
The formation of religious character and a sense of responsibility in students is a challenge for education amid rapid social dynamics and technological developments. Islamic Religious Education (IRE) has a strategic role in internalizing Islamic values, but its learning tends to be cognitive and formal in nature. This study aims to analyze the role of the hidden curriculum of IRE in shaping the religious character and responsibility of students and to formulate a conceptual model of the hidden curriculum of IRE based on an interconnective school ecosystem. Using a qualitative approach, this study employed a case study method at integrated Islamic elementary school. Data collection was conducted through participatory observation, in-depth interviews, and documentation studies. The collected data were then analyzed using thematic analysis techniques. The results of the study explain that the hidden curriculum of PAI is internalized through religious school culture, educator role models, daily habits, and ethical social interactions. Religious values and responsibility are internalized through contextual and continuous learning experiences. This study produced a conceptual model of the hidden curriculum of PAI based on an interconnective school ecosystem, which emphasizes that the character building of students is the result of the integration of the school environment, implicit value education practices, and a continuous internalization process.